Model of Parental Empowerment as Peer Educators in the Prevention of Child Marriage Among Adolescents: A Literature Review - Eka Faizaturrahmi; Nurannisa Fitria Aprianti; Dwi Wirastri (CV. Get Press Indonesia, 2024)
Child marriage is a serious issue affecting adolescents’ health, education, and well-being. This article aims to examine the model of parental empowerment as peer educators in preventing child marriage through a literature review of national and international studies published between 2016 and 2026. The findings indicate that preventing early marriage requires a comprehensive approach involving increased parental knowledge, strengthened parent–adolescent communication, and community-based social norm transformation. Peer education is considered effective in improving knowledge and attitudes and therefore has strong potential to be developed into a sustainable parent-to-parent preventive strategy.